슬관절 전치환술에서 3차원 단층촬영술을 이용한 슬개골의 가상 절제 - Park, Do Young (The Graduate School, Ajou University, 2012)
Background: Though rotational alignment and antero-posterior positioning of the femoral component influences patello-femoral mechanics, it is also significantly influenced by the accuracy of the patellar resection, with the resultant thickness and symmetry of the patella-implant composite Methods: We performed virtual patellar resection with digital software using 3D-CT scans of knees from 49 patients who underwent primary TKR at our hospital, comparing two commonly used resection methods, i.e., the tendon method (TM), and the subchondral method (SCM), to determine an ideal resection plane with respect to the symmetry and thickness of the patellar remnant. Results: The TM gave a thicker resected patella, and a less oval cut surface shape which gives better coverage for a domed prosthesis. Both methods however, gave a symmetric resection both superio-inferiorly as well as medio-laterally. Conclusions: Though TM appears statistically better with respect to the thickness and cut surface shape, only further intra-operative studies with long-term clinical follow up may provide us with the most appropriate patellar resection method.
학위논문(석사)아주대학교 일반대학원 :의학과,2012. 2
Keywords: patella; 3D CT; patellar resurfacing